INNOVATION AS A MEDIATOR FOR FAMILY SUPPORT AND SOCIAL NETWORK TOWARDS WOMEN'S SMES PERFORMANCE - Puspitowati, Ida; Firdausy, Carunia Mulya; Handoyo, Sarwo Edy (Graduate Program of Universitas Tarumanagara, 2023)
Women's SMEs contribute to the economy, so attention to business performance is important to improve. Efforts to improve the performance of women SMEs require knowledge of the factors that play an important role in SME performance. This research was conducted on women SMEs in Belitung district by examining several factors that affect performance, namely social networks, family support and product innovation. In previous studies, there were differences in the results of several researchers on the influence of determining factors on performance, so this research will fill this gap as well as test the role of product innovation as a mediator of social networks and family support on business performance. By using the cross-section method, 113 women’s SMEs were obtained who have been running a business for a minimum of 1.5 years and are engaged in the processing industry. Data analysis with Partial Least Square-Structural Equation Modeling (PLS-SEM), SmartPLS v.4.0 was used in data processing. The path coefficient results show that social network variables and product innovation have a positive and significations effect, while family support has no significations effect on SME performance. Product innovation partially mediates social networks towards women’s SMEs performance, while product innovation fully mediates family support on women’s SMEs performance. Family support has no significations effect towards women’s SMEs performance, this illustrates that women’s SMEs lack family support in their business activities.